Construction site : garbage crew to the rescue! - Rinker, Sherri Duskey (Rinker, Sherri Duskey. Goodnight, goodnight, construction site (Series), 2024)
Before the construction crew can start renovating a fine old neighborhood, they need the help of the garbage vehicles to clean up truckfuls of trash, and much more.